Awareness and Practice of Dental Stem Cells, Bio Banking, and Scaffolds Among Dentists in Tripoli, Libya: A Cross-Sectional Study - Thoraya Elhadi,; Asma Ghoul,; Sumaya Aghila,; Abdulaziz Atia,; Eyman Elhadar, (AlQalam Journal of Medical and Applied Sciences, 2025)
Dental stem cells (DSC) represent a new path to regeneration as they are readily accessible. Their collection is comparatively non-invasive and requires minimal resources. Knowledge of dental stem cells, their source types, preservation methods, ethical considerations, dental uses, preservation length, and so on is essential for their use in regenerative processes. The study sought to assess and compare dental professionals' knowledge, awareness, and practice of dental stem cells and tooth banking. A cross-sectional, questionnaire-based study. The study involved a total of 186 dentists from Tripoli /Libya, who took part in a cross-sectional questionnaire-based survey that assessed the level of knowledge, attitudes, and practices. The participants are dentists who have different academic and professional experiences and who have worked in public sectors such as healthcare centers, dental faculties, as well as private dental clinics. The study was carried out from July to September 2025. The study's findings showed that preserving DSCs for biobanking purposes was significantly more common among dentists with higher academic qualifications, with 82.8% supporting the practice (p = 0.016). When asked about scaffold-supported angiogenesis, academic qualification was significantly associated with beliefs regarding how these technologies improve outcomes (p = 0.006), while clinical experience was not (p = 0.266). When asked about the role of regenerative endodontic awareness, dentists with doctoral degrees (58.6%). This study suggested dental professionals had an acceptable level of understanding, but there is still a need to raise awareness of the current developments on methods of collection, ethical concerns, and guidelines regarding dental stem cells.